2016
DOI: 10.1021/acs.jpcc.6b07032
|View full text |Cite
|
Sign up to set email alerts
|

Spacer Effects of Donor-π Spacer-Acceptor Sensitizers on Photophysical Properties in Dye-Sensitized Solar Cells

Abstract: The donor (D)-π spacer-acceptor (A) framework with electronic push–pull effects provides suitable molecular architectures for molecular design used as efficient light-harvesting sensitizers in dye-sensitized solar cells (DSSCs). Efficiencies of light harvesting and electron injection to the semiconductor of sensitizers play critical roles in DSSC performance. Here, we employed density functional theory to systematically and comparatively investigate the effects of π-spacers of D-π spacer-A types of dyes in sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…This can be explained by less aromatic and more quinoidal nature of DTT-relay (Table 2). 27,28 Analysis of the cyclic voltammograms of compounds 3, 12, 7, 16-18 (Fig. S2 in the Supporting Information) has revealed similar characteristics.…”
Section: Optical and Electrochemical Properties Of Push-pull Chromophmentioning
confidence: 80%
“…This can be explained by less aromatic and more quinoidal nature of DTT-relay (Table 2). 27,28 Analysis of the cyclic voltammograms of compounds 3, 12, 7, 16-18 (Fig. S2 in the Supporting Information) has revealed similar characteristics.…”
Section: Optical and Electrochemical Properties Of Push-pull Chromophmentioning
confidence: 80%
“…al. has reported the red shift and blue shift by varying the number of rings and spacer lengths in D‐π spacer‐accepter dyes . The usage of Th‐, DTT‐ and FL spacers caused red shift when rings were increased to three whereas a blue shift has been observed upon usage of Ph rings with number up to 6.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows UV‐Vis absorption spectra for the dye‐TiO 2 complexes. From previous work, Tan and coworker found that using thiophene based spacers can induce red‐shifts in λmax, in contrast, using phenyl rings as spacers induces a blue‐shift in λ max due to the nonplanarity of spacers. Similarly, we found that D3‐L1‐TiO 2 with thiophene spacer exhibits λ max at 548 nm, while D3‐L2‐TiO 2 with phenyl spacer significantly induces blue‐shift in λ max to 509 nm.…”
Section: Resultsmentioning
confidence: 99%